Simplify the following expression: -10x + 15 - 3x + 2 *

Answers

Answer 1
Answer: = -10x+15-3x+2
= -13x+17

Related Questions

Point Tis on line segment SU. Given TU = 4x + 1, SU = 8, and ST = 3x,determine the numerical length of TU.
Arrow is launched upward at 256 feet per second from top of 85 foot building. What is maximum height of arrow?
Kenny bought 20 packs of baseball cards. There are 12 cards in each pack. How many cards did Kenny buy?
A researcher wanted to determine the prevalence of type 2 diabetes among persons living with HIV in Ojai, a small town in California. He developed a survey questionnaire and mailed to 600 residents of Ojai. The survey asked participants several questions including whether their doctor or health care professional ever told them that they had diabetes. All 600 residents completed the survey and the researcher considered their sample a random sample of the 2,500 total residents of 3 Ojai. The following data was compiled from the survey. The prevalence of diabetes in the sampled survey was 6%. The researcher wanted to compare the prevalence of diabetes by smoking status. In their survey, they found that among 230, who were smokers, 157 reported diabetes and among the remaining nonsmokers, 50 reported diabetes. Construct a two by two table using the data given above. Be sure to label the cells and margins. Diabetes Yes No Smoking Yes a b No с d Total
LAST ATTEMPT IM MARKING AS BRAINLIEST!! (Draw a dilation of the figure using the given scale factor )

(9c^2 + 3c + 9) - (9c^2 + 2c + 7)

Answers

Answer:

c+2

Step-by-step explanation:

Distribute the Negative Sign:

=9c2+3c+9+−1(9c2+2c+7)

=9c2+3c+9+−1(9c2)+−1(2c)+(−1)(7)

=9c2+3c+9+−9c2+−2c+−7

Combine Like Terms:

=9c2+3c+9+−9c2+−2c+−7

=(9c2+−9c2)+(3c+−2c)+(9+−7)

Answer:

c + 2

Step-by-step explanation:

(9c² + 3c + 9) - (9c² + 2c + 7)

9c² + 3c + 9 - 9c² - 2c - 7

9c² + 3c + 9 - 9c² - 2c - 7

c + 2

What is the equation of the line?

Answers

Answer:

A) y=(4)/(7)x

Step-by-step explanation:

The line passes through the origin, so its y-intercept is (0,0). Therefore, we can eliminate choices B and C since they have a y-intercept ≠ 0.

Also recall that the rate of change in a linear function is defined by the change in y divided by the change in x, or the rise/run. We see there's a rise of 4 and a run of 7. Therefore, the slope of the line is 4/7, making choice A correct.

What should be done to both sides of the equation in order to solve y + 8.5 = 17.2?Add 8.5.
Subtract 17.2.
O Add 17.2.
Subtract 8.5.

Answers

Subtract 8.5 from both sides to solve equation.

What is a expression? What is a mathematical equation?

  • A mathematical expression is made up of terms (constants and variables) separated by mathematical operators. A mathematical equation is used to equate two expressions.
  • A mathematical equation is used to equate two expressions. Equation modelling is the process of writing a mathematical verbal expression in the form of a mathematical expression for correctanalysis, observations and results of the given problem.

We have the following equation -

y + 8.5 = 17.2

y + 8.5 - 8.5 = 17.2 - 8.5

y = 8.7

Therefore, Subtract 8.5 from both sides to solve equation.

To solve more questions on Equations, Equation Modelling and Expressions visit the link below -

brainly.com/question/14441381

#SPJ2

Answer:

Subtract 8.5

Step-by-step explanation:

To solve the equation, y has to be isolated (only y will be on one side of the equation)

To do this, we have to get rid of the 8.5, so it has to be subtracted from both sides.

So, the correct answer is subtract 8.5

A trapezoid has an area of 60 square inches. The height of the trapezoid is 5 inches. What is the length of the longer base if the longer base is three times the length of the shorter base?

Answers

Answer:

Step-by-step explanation:

Remark

Let the shorter base = x

Let the longer base = 3x

h = 5

Area = 60

Formula

Area = (b1 + b2)*h /2

Solution

60 = (x + 3x)*5 / 2                Multiply both sides by 2

2*60 = (x + 3x)*5                  Combine like terms

120 = 4x *5

120 = 20x                             Divide by 20

120/20 = x

x = 6

Therefore the two bases are

x = 6

3x = 18

Answer:

C

Step-by-step explanation:

If bd = 7x - 10, BC= 4x - 29, and cd
= 5x - 9, find each value

Answers

Answer:

BD = 88

BC = 27

CD = 61

Explanation:

Given that,

BD = 7x - 10

BC= 4x - 29

CD = 5x - 9

Here we assume BD is a line segment and C is a point lies between B & D.

BD = BC + CD

7x - 10 = 4x - 29 + 5x - 9

Now combine like terms

7x - 10 = 4x + 5x - 29 - 9

7x - 10 = 9x - 38

Move 7x from left hand side to right hand side

-10 = 9x - 7x - 38

-10 = 2x - 38

Add 38 both the side

-10 + 38 = 2x - 38 + 38

28 = 2x

Divide by 2 both the side

x = 14

Now put the value of x and find the length of BD, CD, BC

BD = 7x - 10 = 7*14 - 10 = 98 - 10 = 88

BC= 4x - 29 = 4*14 - 29 = 56 - 29 = 27

CD = 5x - 9 = 5*14 - 9 = 61

That's the final answer.

I hope it will help you.

The value of the expression will be:

BD = 88

BC = 27

CD = 61

How to solve the expression

Given that,

BD = 7x - 10

BC= 4x - 29

CD = 5x - 9

Here we assume BD is a line segment and C is a point lies between B & D.

BD = BC + CD

7x - 10 = 4x - 29 + 5x - 9

Now combine like terms

7x - 10 = 4x + 5x - 29 - 9

7x - 10 = 9x - 38

Move 7x from left hand side to right hand side

-10 = 9x - 7x - 38

-10 = 2x - 38

Add 38 both the side

-10 + 38 = 2x - 38 + 38

28 = 2x

Divide by 2 both the side

x = 14

Now put the value of x and find the length of BD, CD, BC

BD = 7x - 10 = 7*14 - 10 = 98 - 10 = 88

BC= 4x - 29 = 4*14 - 29 = 56 - 29 = 27

CD = 5x - 9 = 5*14 - 9 = 61

Learn more about expressions

brainly.com/question/723406

#SPJ6

Use the quadratic formula to solve the equation 2y^ +6y-8=0

Answers

To solve this problem you must apply the proccedure shown below:

 1. You have the following quadratic equation, which is given in the problem above:

 2y^2+6y-8=0

 2. So, to solve it, you can use the quadratic formula, which is:

 y=(-b
±√(b²-4ac))/2a

 a=2
 b=6
 c=-8

 3. When you susbtitute these values into the formula, you obtain:

 y1=-4
 y2=1